Spatial and Temporal Variability of Suspended-Sediment Concentrations in a Shallow Estuarine Environment - Catherine A Ruhl; David H Schoellhamer (San Francisco Estuary and Watershed Science, 2004)
Shallow subembayments respond differently than deep channels to physical forces acting in estuaries. The U.S. Geological Survey measured suspended-sediment concentrations at five locations in Honker Bay, a shallow subembayment of San Francisco Bay, and the adjacent channel to investigate the spatial and temporal differences between deep and shallow estuarine environments. During the first freshwater pulse of the wet season, the channel tended to transport suspended sediments through the system, whereas the shallow area acted as off-channel storage where deposition would likely occur. Following the freshwater pulse, suspended-sediment concentrations were greater in Honker Bay than in the adjacent deep channel, due to the larger supply of erodible sediment on the bed. However, the tidal variability of suspended-sediment concentrations in both Honker Bay and in the adjacent channel was greater after the freshwater pulse than before. During wind events, suspended-sediment concentrations in the channel were not affected; however, wind played a crucial role in the resuspension of sediments in the shallows. Despite wind-wave sediment resuspension in Honker Bay, tidally averaged suspended-sediment flux was controlled by the flood-dominated currents.